Use of surgical safety checklists in Australian operating theatres: an observational study. Issue 12 (25th May 2016) - Giles, Kristy; Munn, Zachary; Aromataris, Edoardo; Deakin, Anita; Schultz, Timothy; Mandel, Catherine; Maddern, Guy; Pearson, Alan; Runciman, William
Abstract : Introduction: The use of surgical safety checklists (SSC) is an intervention aimed at reducing mortality and morbidity. Although the effectiveness of their use in surgery has been studied extensively, little is known about their practical use in Australian hospitals. The aim of this study was to observe and document the use of SSC in Australia. Methods: This study employed direct observations of checklist use for surgical procedures by trained observers. Medical records were also audited to determine compliance with checklist use and to investigate whether there was any discrepancy between practice (actual care measured by direct observation) and documentation (documented care measured by an audit of records). Results: Among the 11 participating hospitals, overall observed mean completion of the components of the checklist was 27%. Only one hospital used the original World Health Organization checklist. The checklist items most commonly observed to be addressed by the operating theatre staff as noted during observations were: correct patient (99%) and procedure (97%), whether the patient had any allergies (80%), and whether the instrument counts were performed correctly (56%). Findings from the direct observations conflicted with the medical record audit, where there was a higher percentage of completion (86% completion) in comparison to the 27% observed. Conclusion: This is the first study of surgical checklist use within Australia. Overall completion was low across the sites included in this study. Compliance data collected from observations differed markedly from reported compliance in medical records.